A Norma ISO 14005 como instrumento de implementação de sistemas de gestão ambiental em pequenas e médias empresas - de Moraes, Clauciana Schmidt Bueno [UNESP]; Ramos, Luís Henrique Batista [UNESP]; Pugliesi, Erica; Gualter, Leonardo Prudente Torres [UNESP] (My University, 2017)
The use of environmental management systems - EMS based on the requirements of ISO 14001 has shown to be a key tool for addressing the environmental aspects and impacts of an organization. Despite all the benefits that the system provides, we still find many problems in the implementation of EMS, especially in small and medium enterprises - SMEs. Most of the difficulties of implementation is related to intrinsic factors that companies of this size have, and issues related to the models and methods used to implement an EMS. Thus, this work aimed to assess whether the guidelines of ISO 14005:2012 meet the needs of SMEs for the effective implementation of an environmental management system. For it has been identified in the relation between SMEs and EMS the major intrinsic problems of SMEs to implement (PII), such as lack of financial and human resources, and lack of commitment from top management to the SGA. Also was also pointed the main implementation issues related to ISO 14001 (ABNT, 2015) or the models or methods (PIM), highlighting the lack of environmental performance criteria, and the need for a path or sequence of steps for implementation. The study of ISO 14005 (ABNT, 2012) showed that the standard guidelines and implementation examples proposed, include solutions for all problems related to EMS implementation SMEs.
The ISO 14005 standard as implementation instrument for environmental management systems in small and medium enterprises
Keywords: Environmental management; ISO 14005; SMEs; Success factors